Improvisation as a research methodology: exploring links between filmmakers' practice and traditions of enquiry across the academy. Issue 2 (3rd April 2019) - Lees, Dominic
ABSTRACT: This article concentrates on one form of creative practice, improvisation, considering how it has been used as an experimental method within filmmaking as well as in research enquiry. Drawing on my professional experience in the field of narrative fiction filmmaking, as well as interviews with film professionals, I show how a close examination of improvising processes opens up illuminating points of comparison with research methodologies across the academy. This article is an interdisciplinary review, drawing together ideas about improvisation beyond film, looking broadly across the creative arts and most pointedly, drawing an unexpected link between practice research in film and the traditions of laboratory research methodologies within Social Psychology.